SOUTH PRIMORYE, FAR EAST RUSSIA-A KEY REGION FOR GLOBAL PERMIAN CORRELATION - Kotlyar G.V.; Zhuravlev A.V.; Belyansky G.C.; Burago V.I.; Nikitina A.P.; Zakharov Y.D. (My University, 2006)
Significant differences between faunal and floral associations existing in different paleogeographic realms in the Kungurian-Late Permian interval make it difficult to correlate the Permian deposits of the world. Resolving this problem is one of the main tasks of Permian stratigraphy. The global significance of Permian strata of the Primorye region of Far East Russia is enhanced by the specific Middle Permian mixed Tethyan, Boreal and Gondwanan-type brachiopod fauna, mixed Angara-Euromerican-Cathaysian flora, and their close spatial and stratigraphical association with fusulinids, bryozoans, ammonoids, conodonts. These facts permit tracing of global correlational levels of some Permian sequences within the different paleobiogeographical realms: for example, the Monodiexodina sutschanica-Metadoliolina dutkevichi fusulinid zone of the Wordian age and Parafusulina stricta fusulinid zone of the Capitanian age. The Late Permian fauna of the Primorye is mainly Tethyan in origin and provides correlation with similar aged sequences from South China. © 2005 Elsevier Ltd. All rights reserved.
Keywords: Permian; Paleozoic::Permian; Палеозой::Пермская